The short story : an introduction - March-Russell, Paul (Edinburgh University Press, 2009)
This new general introduction emphasises the importance of the short story to an understanding of modern fiction. In twenty succinct chapters, the study paints a complete portrait of the short story - its history, culture, aesthetics and economics. European innovators such as Chekhov, Flaubert and Kafka are compared to Irish, New Zealand and British practitioners such as Joyce, Mansfield and Carter as well as writers in the American tradition, from Hawthorne and Poe to Barthelme and Carver.